2004
DOI: 10.1128/jcm.42.12.5549-5557.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Campylobacter coli , Campylobacter jejuni , Campylobacter lari , and Campylobacter upsaliensis by a Multiplex PCR Developed from the Nucleotide Sequence of the Lipid A Gene lpxA

Abstract: We describe a multiplex PCR assay to identify and discriminate between isolates of Campylobacter coli, Campylobacter jejuni, Campylobacter lari, and Campylobacter upsaliensis. The C. jejuni isolate F38011 lpxA gene, encoding a UDP-N-acetylglucosamine acyltransferase, was identified by sequence analysis of an expression plasmid that restored wild-type lipopolysaccharide levels in Escherichia coli strain SM105 [lpxA(Ts)]. With oligonucleotide primers developed to the C. jejuni lpxA gene, nearly full-length lpxA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 44 publications
5
136
0
5
Order By: Relevance
“…As with RRC026 (ST-21), RRC050 (ST-38), NCSU064 (ST-1162) and RRC043 (ST-1244), the species designations of strains comprising the divergent STs in the secondary cluster were examined further with additional PCR primer sets. Amplification using cadF (Konkel et al, 1999), hipO and lpxA (Klena et al, 2004) primer sets was in agreement with the previously determined C. coli status of these strains.…”
Section: Diversity Of C Coli Alleles and Stssupporting
confidence: 65%
See 2 more Smart Citations
“…As with RRC026 (ST-21), RRC050 (ST-38), NCSU064 (ST-1162) and RRC043 (ST-1244), the species designations of strains comprising the divergent STs in the secondary cluster were examined further with additional PCR primer sets. Amplification using cadF (Konkel et al, 1999), hipO and lpxA (Klena et al, 2004) primer sets was in agreement with the previously determined C. coli status of these strains.…”
Section: Diversity Of C Coli Alleles and Stssupporting
confidence: 65%
“…Finally, the cattle strain RRC043 possessed the novel ST-1244 ST, consisting of six alleles identified previously in C. jejuni or with a high similarity to existing C. jejuni alleles, as well as the C. coli allele uncA17. Even though these strains had been classified originally as C. coli, results typical for C. jejuni were obtained for these three strains with the hipO and lpxA (Klena et al, 2004) primer sets (data not shown). In addition to the alleles within the ST-21, ST-38, ST-1162 and ST-1244 STs, four other divergent alleles were identified.…”
Section: Diversity Of C Coli Alleles and Stsmentioning
confidence: 97%
See 1 more Smart Citation
“…Owing to very weak hippuricase activity of some C. jejuni strains, hippurate-negative strains of C. jejuni are also well recognized (32). Several PCR-based assays have been developed to facilitate the differentiation of C. jejuni from C. coli (4,5,9,15,18,24,33), however the ability of these assays to accurately identify Campylobacter species has not yet been established.…”
mentioning
confidence: 99%
“…Molecular methods using PCR or other nucleic acid techniques have been reported (Klena et al, 2004;Maher et al, 2003;Zhang et al, 2009). For reliable species determination, sequenced PCR products should be compared to published genome sequences of type strains or reference strains from bacterial culture collections.…”
Section: Discussionmentioning
confidence: 99%